2020
DOI: 10.3390/su12187703
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers for Efficient Energy Management Practices in Energy-Intensive Industries: A Case-Study of Iron and Steel Sector

Abstract: The two major reasons behind the world’s energy crisis are losses in energy transmission and less efficient energy use at sinks. The former flaw can be catered by changing the entire energy transmission system which requires investment and planning on a large scale, whereas the later deficiency can be overcome through proper management of energy utilizing systems. Energy-intensive industries have a substantial share in energy consumption and equally high energy saving potentials if they adopt some integrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Not only information campaigns call for public action, but new innovative technologies and infrastructure adaptation requires the public engagement and support (Nuttall, 2012). Institutional effectiveness (D5): Factors like motivation, participation and quality of activities benchmarks institutional effectiveness (Ahmad et al. , 2020).…”
Section: Explanation Of Driversmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only information campaigns call for public action, but new innovative technologies and infrastructure adaptation requires the public engagement and support (Nuttall, 2012). Institutional effectiveness (D5): Factors like motivation, participation and quality of activities benchmarks institutional effectiveness (Ahmad et al. , 2020).…”
Section: Explanation Of Driversmentioning
confidence: 99%
“…Financial stability (D8): Limited access to capital, poor market value affects the adoption of any new plan or policy or practice (Brunke et al. , 2014; Ahmad et al. , 2020).…”
Section: Explanation Of Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Solnørdal and Thyholdt (2017) identified the level of education and cooperation with competitors, universities and research institutions as the primary organizational drivers toward investment in EE. Ahmad et al (2020) reported that the application for the energy-efficient operation was greatly motivated by the need for cost reduction within Pakistan’s iron and steel sectors. Rohdin and Thollander (2006) observed that people with real ambition and a business’ long-term energy strategy were the most critical EE drivers.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Chaotic functions are used with the Coyote Optimization Algorithm in order to attain improved results with a higher convergence speed. The effect of the ten chaotic functions on the RMSE values using COA are shown with the help of boxplots for single diode models of mono-crystalline LSM20 solar module in Figure 20, Photowatt-PWP201 solar The applications of various metaheuristic methods in Solar PV parameter extraction and other industrial application has been discussed in [62][63][64][65][66][67][68].…”
Section: Chaotic Coa For Single Diode Modelmentioning
confidence: 99%